ARTICLE TITLE: THE AUTONOMY OF LINGUISTIC ACQUISITION: A MULTI-DIMENSIONAL FRAMEWORK FOR INDEPENDENT ENGLISH LEARNING IN DOMESTIC ENVIRONMENTS - Khalilov Bakhodir Tolibovich (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article investigates the paradigm shift from institutionalized English Language Teaching (ELT) to self-directed learning models. By synthesizing Cognitive Linguistics, the "Input Hypothesis," and modern AI integration, the paper argues that the home environment, once a secondary study space, has become a primary locus for high-level acquisition. The study explores how micro-immersion, neuroplasticity, and meta-cognitive self-regulation allow independent learners to bypass traditional classroom limitations.